The Complete Writings of Charles Dudley Warner $1 (BVolume 1s - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Complete Writings of Charles Dudley Warner $1 (BVolume 1" by Charles Dudley Warner is a collection of essays written during the late 19th century. The volume features pieces that explore themes of gardening, rural life, and the relationship between humans and nature, offering readers a meditative commentary on the simple pleasures found in tending to the earth. The opening of the book begins with a charming introductory letter that sets the stage for the essays that follow. The author, who is also an editor, expresses a desire to share whimsical and joyous observations about garden life with his readers. Warner emphasizes the richness of life found in simple activities like gardening and the lessons it offers in patience, responsibility, and connection to nature. He humorously recounts his experiences with various plants, the challenges of dealing with weeds and pests, and his reflections on life lessons gained through the art of horticulture. Through engaging prose, he invites readers to appreciate the delights of gardening and its metaphorical ties to personal growth and understanding. (This is an automatically generated summary.)s
My summer in a garden -- Backlog studies -- Baddeck, and That Sort of Thing.
Release date is 2001-06-01
This etext was prepared by David Widger
Keywords: Essays; Nova Scotia -- Description and travel; Baddeck (N.S.) -- Description and travel; Gardening